2013
DOI: 10.1021/jp4101152
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Crystalline Silica Films on Pd(100)

Abstract: Silica films grown on Pd(100) were characterized by Auger electron spectroscopy, low-energy electron diffraction (LEED), and scanning tunneling microscopy (STM). While no evidence of long-range order could be detected for films grown below 600 K, STM images of these films nevertheless revealed flat surfaces through which the step-terrace structure of the substrate could be seen. Annealing the films in 10 −6 Torr of O 2 above 975 K resulted in crystalline bilayers that produced hexagonal LEED patterns with a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 44 publications
6
82
0
Order By: Relevance
“…Previously we found that three-dimensionally disordered silica fi lms were diffi cult to image without the tip changing the surface, indicating a diffi culty in establishing stable tunneling. [ 11 ] Inspired by this earlier fi nding, it is suggested that the dramatic decrease in tip-sample distance as the imaging bias was raised toward the Fermi level at this location may be associated with the breakdown of the bilayer structure weakening the coupling to the metal surface.…”
Section: Doi: 101002/admi201400108mentioning
confidence: 86%
See 3 more Smart Citations
“…Previously we found that three-dimensionally disordered silica fi lms were diffi cult to image without the tip changing the surface, indicating a diffi culty in establishing stable tunneling. [ 11 ] Inspired by this earlier fi nding, it is suggested that the dramatic decrease in tip-sample distance as the imaging bias was raised toward the Fermi level at this location may be associated with the breakdown of the bilayer structure weakening the coupling to the metal surface.…”
Section: Doi: 101002/admi201400108mentioning
confidence: 86%
“…[ 21 ] More prolonged annealing of multilayer fi lms led to additional silica loss and eventually the appearance of crystalline diffraction patterns. The crystalline phase could also be prepared by depositing ≈2 ML SiO 2 under the above conditions followed by annealing above 970 K. [ 11 ] The position and shape of the Si LVV AES peak indicated that the as grown and annealed fi lms were SiO 2 . The STM images were collected at room temperature with W tips at tunneling currents between 0.1 and 0.55 nA; over this range the tunneling current did not noticeably affect the images.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that the thinnest silica film forms a hexagonal layer of corner-sharing [SiO 4 ] tetrahedra (referred to as "silicatene" in analogy to graphene [5]) which is strongly bound to a metal support through Si-O-Metal linkages [6]. On noble metals such as Ru(0001), Pd(100) and Pt(111), double-layer (or bilayer) silicate films may be grown, which are weakly bound to the support via dispersive forces [7][8][9][10]. In this case, a relatively large space between the silicate sheet and the metal support allows, in principle, small molecules to intercalate the interface, diffuse and ultimately react on the metal surface.…”
Section: Introductionmentioning
confidence: 99%